Peningkatan Literasi Uang Digital Melalui Edukasi dan Implementasi QRIS di Desa Kineppen, Kab. Karo, Kec. Munte - Aulia Rahma; Naila Haya Fauziah; Reydina Pasya Amanda; Siti Aisyah; Tuti Anggraini (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to improve digital money literacy among the community of Kineppen Village, Munte District, Karo Regency, through education and the implementation of the QRIS (Quick Response Code Indonesian Standard) payment system. The research utilized a descriptive qualitative approach, incorporating field observations, interviews, and direct mentoring with four local businesses: Ayam Penyet Pak Lek, Warkop Aim Tigander, Oke Laundry Kineppen, and Pangkas Singarimbun. The findings show that two businesses, Ayam Penyet Pak Lek and Pangkas Singarimbun, successfully adopted QRIS, leading to smoother transactions and increased customer trust. However, the other two businesses, Warkop Aim Tigander and Oke Laundry Kineppen, still face challenges in adopting the system due to limited internet access and deep-rooted traditional cash payment habits. Despite these barriers, the program significantly enhanced the digital literacy of local entrepreneurs, raising their awareness and readiness to participate in the village’s digital economy. This study emphasizes the importance of continuous support and access to technology in fostering the broader adoption of digital payment systems, particularly in rural areas where technological access may still be limited